Soluble CD146, a biomarker and a target for preventing resistance to anti-angiogenic therapy in glioblastoma - Ahmad Joshkon; Emeline Tabouret; Wael Traboulsi; Richard Bachelier; Stéphanie Simoncini; Sandrine Roffino; Carine Jiguet-Jiglaire; Bassam Badran; Benjamin Guillet; Alexandrine Foucault-Bertaud; Aurelie S. Leroyer; Françoise Dignat-George; et al. (Acta Neuropathologica Communications, 2022)
Abstract Rationale Glioblastoma multiforme (GBM) is a primary brain tumor with poor prognosis. The U.S. food and drug administration approved the use of the anti-VEGF antibody bevacizumab in recurrent GBM. However, resistance to this treatment is frequent and fails to enhance the overall survival of patients. In this study, we aimed to identify novel mechanism(s) responsible for bevacizumab-resistance in CD146-positive glioblastoma. Methods The study was performed using sera from GBM patients and human GBM cell lines in culture or xenografted in nude mice. Results We found that an increase in sCD146 concentration in sera of GBM patients after the first cycle of bevacizumab treatment was significantly associated with poor progression free survival and shorter overall survival. Accordingly, in vitro treatment of CD146-positive glioblastoma cells with bevacizumab led to a high sCD146 secretion, inducing cell invasion. These effects were mediated through integrin αvβ3 and were blocked by mucizumab, a novel humanized anti-sCD146 antibody. In vivo, the combination of bevacizumab with mucizumab impeded CD146 + glioblastoma growth and reduced tumor cell dissemination to an extent significantly higher than that observed with bevacizumab alone. Conclusion We propose sCD146 to be 1/ an early biomarker to predict and 2/ a potential target to prevent bevacizumab resistance in patients with glioblastoma.